Practitioner-informed improvements to early childhood intervention performance checklists and practice guides - Dunst, Carl J.; Hamby, Deborah W.; Wilson, Linda L.; Espe-Sherwindt, Marilyn; Nelson, Donna E. (REID (Research and Evaluation in Education), 2017)
Results from four early childhood practitioner field tests of performance checklists and early intervention practice guides are reported. Findings from the first field test were used to make changes and improvements in the checklists and practice guides evaluated in the second and third field tests, and findings from the latter two field tests were used to improve the checklist and practice guide evaluated in the fourth field test. Results indicated that changes made in response to practitioners' suggestions and feedback were associated with (1) progressive increases in the practitioners' social validity judgments of the checklists, practice guides, and checklist-practice guide correspondence, and (2) progressive decreases in the number of practitioner suggestions and feedback for improving the early intervention materials. The field-test research demonstrates the importance of practitioner input, suggestions, and feedback for improving the usefulness of early childhood intervention practices.